Implementation of Chest Physiotherapy and Nebulizer Therapy for a Pneumonia Patient with Ineffective Airway Clearance: A Case Report - Yuly Peristiowati; Bayu Adi Prasetya; Darwis Alvian Bahari Nafi; Hariyono Hariyono (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2026)
Pneumonia is one of the leading causes of morbidity and mortality in humans, often accompanied by ineffective airway clearance due to secretion accumulation. Chest physiotherapy and nebulizer therapy are essential nursing interventions to facilitate secretion clearance and maintain airway patency in such conditions. Objective: This study aims to comprehensively describe the implementation of chest physiotherapy and nebulizer therapy in pneumonia patients with ineffective airway clearance. Methods: This case study involved two pediatric patients aged 50 years with a medical diagnosis of pneumonia who were admitted to the Graha Mandiri Ward, 3rd Floor. Data collection was conducted through assessment, intervention, nursing implementation over three days, and evaluation using observation and documentation techniques. Results: The patients presented with primary complaints of shortness of breath, cough, and runny nose, accompanied by physical findings such as tachypnea, intercostal retractions, and crackles in the lungs. The established nursing diagnosis was ineffective airway clearance. Chest physiotherapy and nebulizer therapy were implemented according to standard procedures. Evaluation showed that the implementation of chest physiotherapy and nebulizer therapy successfully facilitated secretion clearance and improved the patient’s airway clearance, as evidenced by reduced shortness of breath and decreased abnormal breath sounds. Conclusion: The implementation of chest physiotherapy and nebulizer therapy is effective in addressing the issue of ineffective airway clearance in patients with pneumonia. It is recommended that nurses optimize education for families regarding the importance and procedures of chest physiotherapy and nebulizer therapy, as well as environmental factors that affect respiratory health